Grassroots leadership and the arts for social change - Erenrich, Susan J.; Wergin, Jon F. (Building leadership bridges,, 2017)
Throughout history artists have led grassroots movements of protest, resistance, and liberation. They created dangerously, sometimes becoming martyrs for the cause. Their efforts kindled a fire, aroused the imagination and rallied the troops culminating in real transformational change. Their art served as a form of dissent during times of war, social upheaval, and political unrest. Less dramatically perhaps, artists have also participated in demonstrations, benefit concerts, and have become philanthropists in support of their favorite causes. These artists have been overlooked or given too little attention in the literature on leadership, even though the consequences of their courageous crusades, quite often, resulted in censorship, blacklisting, imprisonment, and worse. This forthcoming book seeks to explore the intersection of grassroots leadership and the arts for social change by accentuating the many victories artists have won for humanity. Through this forthcoming book readers will vicariously experience the work of these brave figures, reflect on their commitments and achievements, and continue to dream a better world full of possibility.